Early Thymectomy Is Associated With Long-Term Impairment of the Immune System: A Systematic Review - Cavalcanti, Nara Vasconcelos; Palmeira, Patrícia; Jatene, Marcelo Biscegli; de Barros Dorna, Mayra; Carneiro-Sampaio, Magda (Frontiers in Immunology, 2021)
Background and Aims Congenital heart diseases (CHDs) are diagnosed in approximately 9 in 1,000 newborns, and early cardiac corrective surgery often requires partial or complete thymectomy. As the long-term effect of early thymectomy on the subsequent development of the immune system in humans has not been completely elucidated, the present study aimed to evaluate the effects of thymus removal on the functional capacity of the immune system after different periods. Methods A systematic review of the literature was performed using MEDLINE, EMBASE, LILACS and Scopus. The inclusion criteria were original studies that analyzed any component of the immune system in patients with CHD who had undergone thymectomy during cardiac surgery in the first years of life. The results were evaluated for the quality of evidence. Results Twenty-three studies were selected and showed that patients who underwent a thymectomy in the first years of life tended to exhibit important alterations in the T cell compartment, such as fewer total T cells, CD4+, CD8+, naïve and CD31+ T cells, lower TRECs, decreased diversity of the TCR repertoire and higher peripheral proliferation (increased Ki-67 expression) than controls. However, the numbers of memory T cells and Treg cells differed across the selected studies. Conclusions Early thymectomy, either partial or complete, may be associated with a reduction in many T cell subpopulations and TCR diversity, and these alterations may persist during long-term follow-up. Alternative solutions should be studied, either in the operative technique with partial preservation of the thymus or through the autograft of fragments of the gland. Systematic Review Registration Prospero [157188].